Detection of single line to ground fault and self-extinguishing by using a variable and a fixedable inductance in distribution grid in power - Jabbar, Feryal Ibrahim; Soomro, Dur Muhammad; Abdullah, Mohd Noor bin; Radzi, Nur Hanis binti Mohammad; Baloch, Mazhar Hussain; Rahmoon, Asif Ahmed; Fakhruldeen, Hassan Falah (Institute of Advanced Engineering and Science, 2023)
This paper tackled the method for determining the number of Peterson coil which is can compensate with the capacitance because it is important in determining the state of parallel resonance, which in turn control the ground fault current and make the approximate value of the current equal to the current in the sound phases. In this way, we can protect the electrical devices and equipment from being damaged by residual current resulting from the arc due to ground fault, which increases the temperature of conductors which are to a breakdown of insulators and damaging them. Ground fault current equals three times the actual current, and its effect depends on two types of variables which are the first: the number of Peterson coils (which specify the inductance value and compensated) and second: the period time of extinguishing electric are in the ground fault. we obtain, by experimental in the lab where it using the servo motor to control the number of Peterson coils which in turn specify the variable and invariable inductance. We have obtained optimal results for the value of ground-fault current, detect the ground fault and treat it without effect of network load and without power cut off for consumer.